Women power! Gender-related inequality in agricultural income generation: Empirical evidence from eight African countries - Heesemann, Esther; Kluth, Jessika; Nico, Gianluigi; Cavatassi, Romina; Sitko, Nicholas; Azzarri, Carlo (International Food Policy Research Institute, 2023)
Gender disparities in climate change vulnerability not only reflect preexisting gender inequalities, but they also reinforce them. Inequalities in the ownership and control of household assets and rising familial burdens due to male outmigration, declining food and water access and increased disaster exposure can undermine women’s abilities to achieve economic independence. Our study looks at gender-related inequality and climate vulnerability, aiming at quantifying how climate shocks and stressors influence income and agriculture-related outcomes across households, with differing levels of gender equality in agricultural decision-making, and estimating to what extent gendered differences in productivity, income, labor, and farm investments are affected by exposure to climate shocks. Our study takes advantage of nationally representative LSMSISA household surveys from eight countries in Africa, south of the Sahara (Burkina Faso, Ethiopia, Malawi, Mali, Niger, Nigeria, Tanzania, and Uganda), matched with gridcell monthly time-series bioclimatic variables (temperature, rainfall, SPI, SPEI), to identify climate shocks and weather variability. We use a multivariate regression framework to estimate elasticities of climate shocks, capturing also nonlinearities along the distributions of outcome variables using a quantile regression model. Results show that climate shocks and weather variability exert a disproportionate negative effect on women in all dimensions considered that call for local advocacy initiatives in support of labor market policies for climate adaptation. Sustainable, 40 BOOK OF ABSTRACTS climate-resilient policies and interventions on the labor market remain a key priority, alongside vulnerable group protection in planning and promoting agriculture- and job-related programs.